The association between different forms of organizational trust and correctional staff job stress - Haynes, Stacy H. (Journal of crime and justice, 2020)
Trust is crucial to the proper functioning of organizations. Trust has been examined at many levels, and researchers have recently expanded the study of trust to include areas ranging from the neuroscience of trust to the influence of institutional trust on product sales and marketing. While academic interest in trust has grown, research on trust and job stress among correctional employees is rare. The current study evaluated the relationships between three types of trust (coworker, supervisor, and management trust) and correctional staff job stress. Using staff survey data from a Southern prison, two multivariate OLS regression equations were estimated - one for all surveyed staff and a second for the subgroup of correctional officers - in order to determine how the three types of organizational trust related to job stress. Results indicated that trust in coworkers mattered for correctional officers only and that trust in supervisors and management had a greater influence on job stress both for all correctional staff and for the subgroup of correctional officers. Specifically, those with higher levels of supervisor and management trust reported lower levels of job stress.